2015
DOI: 10.1063/1.4915133
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated, field-portable microscopy platform for clinical diagnostic applications

Abstract: Clinical microscopy is a versatile diagnostic platform used for diagnosis of a multitude of diseases. In the recent past, many microfluidics based point-of-care diagnostic devices have been developed, which serve as alternatives to microscopy. However, these point-of-care devices are not as multi-functional and versatile as clinical microscopy. With the use of custom designed optics and microfluidics, we have developed a versatile microscopy-based cellular diagnostic platform, which can be used at the point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…is receiving increased attention at recent conferences and the current chemistry literature. 125 In this overview paper, wireless communications standards are briefly reviewed and are evaluated with emphasis on their potential applicability for data acquisition of transient optical emission spectrometry signals in the field from PMT or PDA detectors. Evaluation criteria included (among others) portability, electrical power consumption, and speed of communications.…”
Section: Introductionmentioning
confidence: 99%
“…is receiving increased attention at recent conferences and the current chemistry literature. 125 In this overview paper, wireless communications standards are briefly reviewed and are evaluated with emphasis on their potential applicability for data acquisition of transient optical emission spectrometry signals in the field from PMT or PDA detectors. Evaluation criteria included (among others) portability, electrical power consumption, and speed of communications.…”
Section: Introductionmentioning
confidence: 99%
“…The malarial parasite, Plasmodium infects RBCs and the infected RBCs display morphological features that are different from normal RBCs. Through IFC and a custom-built smartphone application, it was possible to differentiate between infected and normal cells, and obtain a quantitative value of the parasitemia levels 49 . Thus, the combination of IFC and microfluidics could possibly be a low-cost alternative to conventional detection schemes, such as clinical microscopy.…”
Section: Advancement Of Microfluidics In the Indian Contextmentioning
confidence: 99%
“…Specifically the papers published in this special issue include, fast fluorescence imaging techniques (Jabbar et al, 21 Cha et al 22 ), Super-resolution (You et al 23 ), portable Microscopy (Jagannadh et al 24 ), Multiphoton Microscopy (Ehmke et al 25 ), Image Reconstruction Techniques (Venkatesh et al 26 ) and application in the field of Medicine/Biology (Mandal et al, 27 Rai et. Al.…”
Section: The Special Issue and The Promise Of Emerging Techniquesmentioning
confidence: 99%
“…Ehmke et al 25 report an optimized and efficient multiphoton microscopy technique for imaging highly-ordered biological tissue whereas, Venkatesh et al 26 propose signal processing techniques such as, Directional filters for high quality (noise-free and edge-preserving) fluorescence imaging. Jagannadh et al 24 proposed and demonstrated low-cost and portable variant of optical microscope. This may have application in rural health-care and clinical diagnosis.…”
Section: The Special Issue and The Promise Of Emerging Techniquesmentioning
confidence: 99%